African Swine Fever Diagnosis Adapted to Tropical Conditions by the Use of Dried‐blood Filter Papers. Issue 4 (27th November 2014) - Randriamparany, T.; Kouakou, K. V.; Michaud, V.; Fernández‐Pinero, J.; Gallardo, C.; Le Potier, M.‐F.; Rabenarivahiny, R.; Couacy‐Hymann, E.; Raherimandimby, M.; Albina, E.
Summary: The performance of Whatman 3‐MM filter papers for the collection, drying, shipment and long‐term storage of blood at ambient temperature, and for the detection of African swine fever virus and antibodies was assessed. Conventional and real‐time PCR, viral isolation and antibody detection by ELISA were performed on paired samples (blood/tissue versus dried‐blood 3‐MM filter papers) collected from experimentally infected pigs and from farm pigs in Madagascar and Côte d'Ivoire. 3‐MM filter papers were used directly in the conventional and real‐time PCR without previous extraction of nucleic acids. Tests that performed better with 3‐MM filter papers were in descending order: virus isolation, real‐time UPL PCR and conventional PCR. The analytical sensitivity of real‐time UPL PCR on filter papers was similar to conventional testing (virus isolation or conventional PCR) on organs or blood. In addition, blood‐dried filter papers were tested in ELISA for antibody detection and the observed sensitivity was very close to conventional detection on serum samples and gave comparable results. Filter papers were stored up to 9 months at 20–25°C and for 2 months at 37°C without significant loss of sensitivity for virus genome detection. All tests on 3‐MM filter papers had 100% specificity compared to the gold standards. Whatman 3‐MM filter papers have the advantage of being cheap and of preserving virus viability for future virus isolation and characterization. In this study, Whatman 3‐MM filter papers proved to be a suitable support for the collection, storage and use of blood in remote areas of tropical countries without the need for a cold chain and thus provide new possibilities for antibody testing and virus isolation.